How a Minahasan Child Acquires English: A Case Study of a Foreign Language Young Learner - Tololiu, Sharon Clarisa; Sinadia, Alfrits Roul (Procedia of Social Sciences and Humanities, 2024)
The background of this study is the need to investigate how a foreign language young learner in Indonesian context acquires English using internet technology media. Specifically, it studied how an Indonesian child learns to speak English through the activities of watching English videos on YouTube and how the environment plays its roles in influencing the child’s success of learning English through the media. This research used the qualitative case study approach, and the data were gathered through interviews and observations. The main result found in the study is that watching English videos through YouTube is effective in helping the child acquire English.